2022
DOI: 10.2147/prbm.s370339
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Educational Anxiety Under the “Double Reduction” Policy Based on the Family and Students’ Personal Factors

Abstract: Introduction Educational anxiety is a true portrayal of Chinese parents. As an endogenous problem in the development of modern education system, the pressure of students’ entrance examination continues to rise. Methods Based on the empirical survey data of education in 3298 families, this study uses the analysis method of multiple linear regressions to analyze the influencing factors of parental education anxiety and finds that educational anxiety has become a common so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…24 Teachers are among the professionals who work on the front line of childhood and adolescent trauma by hearing, seeing, and responding to students' traumas, contributing to emotional burdens, stress, and anxiety. 23,25 While some scholars consider STS a type of Burnout, most have considered it as one aspect of compassion fatigue, BO being the other aspect. 24 The introduction of online teaching and learning has resulted in teachers' stress and anxiety, especially for those with low ICT competence.…”
Section: Teachers' Secondary Traumatic Stress During the Covid-19 Pan...mentioning
confidence: 99%
See 1 more Smart Citation
“…24 Teachers are among the professionals who work on the front line of childhood and adolescent trauma by hearing, seeing, and responding to students' traumas, contributing to emotional burdens, stress, and anxiety. 23,25 While some scholars consider STS a type of Burnout, most have considered it as one aspect of compassion fatigue, BO being the other aspect. 24 The introduction of online teaching and learning has resulted in teachers' stress and anxiety, especially for those with low ICT competence.…”
Section: Teachers' Secondary Traumatic Stress During the Covid-19 Pan...mentioning
confidence: 99%
“… 3 The situation has increased anxiety and frustration, affecting their academic achievement. 5 , 25 , 30 A study conducted in the US indicated that 72% of students had a high level of stress than usual. In comparison, 73% of respondents expressed fears related to depression, anxiety, and other mental health issues associated with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Parental educational anxiety has thus become an important issue within family education in China [ 26 ]. In 2018, the results of a survey of 3205 parents across the country revealed the anxiety index score of Chinese parents as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, preschool teachers noted that parents who experienced educational anxiety relating to the transition tended to imagine their children in a highly demanding environment during their first year of school [ 5 ]. The gap in parental expectations has a significant positive effect on parental educational anxiety, with a wider gap corresponding to higher levels of parents’ educational anxiety [ 26 ]. Parental concerns regarding their children’s readiness appear to be linked to their awareness that their children would not fulfill and/or meet academic and social expectations in their new environments [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation